A carbon nanosphere nanofluid for improving the toughness and thermal properties of epoxy composites. (10th September 2022) - Li, Peipei; Qu, Danyao; Zhang, Lu; Su, Chen; Ma, Jie; Wang, Qi; Liu, Chao; Wang, Yongkun; Feng, Huanran; Li, Cong; Wu, Weiwei
Abstract: A carbon nanosphere nanofluid (CNS-nanofluid) was successfully prepared through the non-covalent modification of carbon nanosphere (CNS) with the specific ionic liquid (i.e. [M2070][VBS]) at first. The resulting CNS-nanofluid is a homogeneous and stable fluid with liquid-like behaviour at room temperature, and which shows better dispersion stability in its good solvents and improved processability than the pristine CNS. Subsequently, this CNS-nanofluid was used as a kind of novel functional filler and incorporated into epoxy matrix to prepare the CNS-nanofluid filled epoxy composites (CNS-nanofluid/EP composites). The toughness and thermal properties of those CNS-nanofluid/EP composites were carefully characterized and analysed. And it was found that this CNS-nanofluid could respectively improve the impact toughness and glass transition temperature of the CNS-nanofluid/EP composites to 19.8 kJ m −2 and 122.5 °C at the optimum amount, demonstrating that this CNS-nanofluid is a kind of promising functional filler to achieve robust epoxy composites, and thus opening up new possibilities with great significance for epoxy composites in high-performance applications.